Apparent diffusion coefficient of oxygen and corrosion control of reinforcement rebar coated with primers - Pazini, Enio; Andrade, Carmen (Revista ALCONPAT, 2018)
The present work evaluates the influence of different primers applied in the reinforcement steel on the apparent diffusion coefficient of oxygen (Dap (O2)) and on the corrosion intensity (Icorr), comparing the results with a reference cimentitious mortar. Oxygen flow (J (O2)) until the reinforcement steel was measured by potenciostático method in steady state. The Icorr was monitored by the Polarization Resistance technique (Rp). Evaluations related porosity of the primers were made through magnifying glasses, optical microscopy and SEM. Primers that represent barrier protection systems proved to be less permeable to oxygen. The Dap (O2) values ranged from 2.1 x 10-6 cm2/s to 4 x 10-9 cm2/s, causing variation in the Icorr due to cathodic control of the corrosion process.